PERAN KOMUNIKASI ORANG TUA DALAM MENINGKATKAN KECERDASAN BAHASA ANAK USIA DINI - Nuryani, Nuryani; Herlina, Herlina; Bachtiar, Muhammad Yusri; Wahira, Wahira (MAJU : Indonesian Journal of Community Empowerment, 2025)
Communication skills are the ability of a person who is able to convey all information through his mind in the form of meaningful, logical, and systematic expressions possessed by early children. In simple terms, language skills can be interpreted as the ability of children to talk and interact with their friends and environment. Thus, children's communication skills can develop. Based on the results of the researcher's observations, there are still some children who experience delays in terms of communication, such as children who cannot use Indonesian properly and correctly, can only use English and children still look sloppy in expressing words. The objectives of this study are (1) to describe the role of parents as guides in developing early childhood communication skills in RA and (2) to describe the role of parents as educators in developing early childhood communication skills in RA group B in RA Tathmainnul qulub. This study uses a qualitative approach with a special type of study research. Data collection was carried out by observation, interview, and documentation techniques. The data validity technique is carried out by triangulation of methods, time and sources. The data analysis technique uses Miles and Huberman model analysis with steps: data reduction, data presentation, and conclusion or verification. providing basic education, basic skills, affection, a sense of security, and instilling good habits in children, providing child assistance, support or motivation, and information on how to learn well and appropriately.